Life prediction of P91 piping accounting for creep fatigue conditions. (4th July 2022) - Lo Conte, A.; Bassi, F.; Beretta, S.; Foletti, S.; Cristea, M. E.
ABSTRACT: To address the lack of available standard codes that deal with interactions between creep and fatigue, which is generally approached with a simple superposition law, the ( C t ) a v g parameter associated with CFCG is introduced, under the hypothesis of partial creep strain reversal based on the creep reversal parameter C R . The TDFAD methodology used to predict initial crack growth during creep and creep-fatigue regime with P91 grade steel operating at 600°C is reviewed and integrated. This state-of-the-art crack tip parameter is introduced and accounts for small-scale creep, in the creep-fatigue crack propagation assessment.